Melatonin as a regulator of apoptosis in leukaemia: molecular mechanism and therapeutic perspectives - Mafi, Alireza; Rismanchi, Hamidreza; Gholinezhad, Yasaman; Mohammadi, Mohaddese Malek; Mousavi, Vahide; Hosseini, Seyed Ali; Milasi, Yaser Eshaghi; Reiter, Russel J.; Ghezelbash, Behrooz; Rezaee, Malihe; Sheida, Amirhossein; Zarepour, Fatemeh; et al. (Frontiers in Pharmacology, 2023)
Leukaemia is a dangerous malignancy that causes thousands of deaths every year throughout the world. The rate of morbidity and mortality is significant despite many advancements in therapy strategies for individuals who have been affected. Most of antitumor medications used now in clinical oncology employ apoptotic signalling pathways to induce cancer cell death. Accumulated data have shown a direct correlation between inducing apoptosis in cancer cells with higher tumour delay regression and survival. Until now, the efficacy of melatonin as a powerful antitumor agent has been firmly established. The change in melatonin concentrations was reported in multiple tumours such as endometrial, hematopoietic and breast cancers. Findings show that melatonin's anticancer properties, such as its pro-oxidation function and ability to promote apoptosis, point to the possibility of utilizing this natural substance as a promising agent in innovative cancer therapy approaches. Melatonin stimulates cell apoptosis via regulating of many apoptosis facilitators, including mitochondria, cytochrome c, Bcl-2, production of reactive oxygen species (ROS), and apoptosis receptors. The aim of this paper, we intended to further assess the anticancer effects of melatonin through the apoptotic pathway considering the role that cellular apoptosis plays in the pathogenesis of cancer. This effect of melatonin may be appropriate for usage as an adjuvant along with other therapeutic approaches such as radiotherapy and chemotherapy.